TOBACCO OBSERVER VOLUME 13 NUMBER 2 (Tufts Archival Research Center, 2007)
Issue of Tobacco Observer dedicated to issues surrounding in-flight smoking. Includes a piece on Northwest Airlines' ban on smoking, and argues that it should focus instead on safety, maintenance, and passenger satisfaction issues. Discusses cabin air quality and the minimal research on the subject, and claims that environmental tobacco smoke (ETS) in the cabin air is minimal. Interviews Larry Holcomb, citing the lack of scientific evidence that ETS is harmful. Summarizes federal regulatory activity.